The Impact of the COVID-19 Pandemic in Townships and Lessons for Urban Spatial Restructuring in South Africa - SANELE BRIAN MBAMBO; SAMUEL BABATUNDE AGBOLA (African Journal of Governance and Development, 2020)
The footprints of the injustices of apartheid spatial planning remains visible in South Africa, especially in the nation’s peri-urban settlements, exemplified in poorly planned and densely populated townships. COVID-19 added to the socio-economic challenges of these areas due to their spatial configuration, dense population, generally poor sanitation and poor transport planning. These factors made the operationalization of the pandemic’s dictates, such as washing of hands and social distancing, difficult, if not impossible. This paper examines how the spatial organization and the various attributes of townships in South Africa affect government’s attempt at curtailing the COVID-19 pandemic in these areas. The paper contextualises the various government regulations aimed at curbing the spread of the virus, with a view to learning significant lessons for urban spatial restructuring. The paper is based mainly on a thematic and contextual analysis of secondary data, including published and unpublished literature, especially government regulations and activities on the pandemic in the study area. These are augmented with national and international documented experiences of the pandemic. Findings show that settlement overcrowding, poor restructuring and unresolved land restitution frustrate government’s interventions to control the spread of COVID-19 in KwaMashu and other South African townships. The paper concludes by making recommendations that highlight the need for innovative methods to accelerate the refurbishment of poorly planned townships; increased attention to informal settlement upgrading; and a land reform programme. These will make the actualisation of future government plans easier in the case of future epidemics and other emergencies.